(untitled) (Research, Society and Development, 2021)
Mycorrhizal associations are strategies used by most vascular plants, in order to increase the area of ​​absorption of water and nutrients. However, the establishment of this association is modeled by environmental factors, including rainfall. The aim of this study was to evaluate the relationship between rainfall and microrrizic colonization in rosewood and mahogany plants. Collections of roots and rhizospheric soils were carried out in August / 2005, December / 2005 and March / 2006. The variables analyzed were the percentage of mycorrhizal colonization (%), the intensity of colonization (%) and the density of spores in the soil under planting. In general, mycorrhizal colonization was greater in the root system of rosewood. Mycorrhizal spores showed a marked seasonal variation, with greater density recorded in the rhizosphere of the rosewood in the month of March, and mahogany in the month of December. The average colonization of roots by FMA was influenced by water availability, with a higher rate of colonization and spores in the period of greatest amount of rainfall. Mahogany showed higher concentrations of Ca, Mg and lower concentrations of Mn in the leaves than rosewood. Both species showed the same macronutrient concentration sequences in the leaves: Ca> K> Mg> P. The sequence of micronutrient concentration in the leaves on the rosewood was Fe> Mn> Zn and on the mahogany, it was Fe> Zn> Mn. There was a significant positive correlation between root colonization by arbuscular mycorrhizal fungi and levels of Ca and Mg in the leaves of the rosewood in the month of December and, negative for the levels of Zn in the leaves of the mahogany in the months of March and December.